Dielectric Slab Eigen-Wave Diffraction by Periodic Grating of Rectangular Patches pectroscopy - Karvitsky, G. E.; Prosvirnin, S. L. (Видавничий дім «Академперіодика», 2012)
Dielectric Slab Eigen-Wave Diffraction by Periodic Grating of Rectangular Patches pectroscopy